Psikologi Perkembangan Anak Usia Dini - Fauziah Nasution; Klara Putri Ningsih; Tania May Sabrina Nasution; Desy Kartika Dewi (Pusat Riset dan Inovasi Nasional, 2024)
This research discusses complex problems in child development psychology, especially those experienced in the family environment. Difficulty in educating children who do not meet expectations can hinder growth and development according to their age. The family environment has a crucial role as a good educator, meeting standards as a necessity for parents. Failure in this case has a serious impact on the psychology of child development, because of the close relationship between parents and children to support their future. The importance of the family environment, especially the role of parents, as the first education for child development psychology is the main focus of this research. The child's development process in language, physical-motor and emotional aspects requires critical support from the family environment as capital for the child's future life. Early childhood experiences a vulnerable phase called the Golden Age, where their development experiences a significant spike and does not repeat itself in the following age period. Developmental psychology is defined as qualitative changes in an individual's personality, more than quantitative changes. Child development includes physical, intellectual, social, linguistic, emotional, moral and religious aspects, all of which are integrated into one whole. This research describes the complexity of an individual's life personality development, distinguishing from various main aspects, including physical and motoric, intellectual, social, language, emotional, moral and religious. The findings from this research provide in-depth insight into how the family environment can play a critical role in shaping a child's development, with major implications for that individual's well-being and future.